2022
DOI: 10.3390/ijerph19148748
|View full text |Cite
|
Sign up to set email alerts
|

How Daily Obstacles Affect Frontline Healthcare Professionals’ Mental Health during Omicron: A Daily Diary Study of Handwashing Behavior

Abstract: Based on coping theory, the current research examines how and why COVID-19 phobia affects frontline healthcare professionals’ mental health, as well as their burnout and work-related stress. We focused on the mediating role of burnout and work-related stress in this study. In the current study, we also examined the moderating influence of healthcare professionals’ handwashing behavior using the Hayes Process model. We employed a daily diary approach to collect data from respondents in Pakistan’s frontline heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 103 publications
0
7
0
Order By: Relevance
“…While constructs were examined at various phases, CMB remains a viable option. As a result, the objective of this investigation was to overcome potential CMB issues and analyze the novelty of models using CFA (Khan et al, 2022). Initially, the researchers ran CFA with all model components such as migratory stress, perceived COVID-19 (PC-19) threat, psychological distress, resilience, PGD, and death anxiety.…”
Section: Results For Studymentioning
confidence: 99%
“…While constructs were examined at various phases, CMB remains a viable option. As a result, the objective of this investigation was to overcome potential CMB issues and analyze the novelty of models using CFA (Khan et al, 2022). Initially, the researchers ran CFA with all model components such as migratory stress, perceived COVID-19 (PC-19) threat, psychological distress, resilience, PGD, and death anxiety.…”
Section: Results For Studymentioning
confidence: 99%
“… 20 21 Critically, our findings extend occupation-specific and hand hygiene-specific findings during the COVID-19 pandemic, including associations between burnout symptoms and (1) reduced hand hygiene among healthcare workers in China, 34 (2) reduced personal protective equipment adherence and hand hygiene among healthcare workers in Malaysia 35 and (3) reduced handwashing behaviours among restaurant kitchen chefs in China. 36 Interestingly, a moderation analysis conducted on frontline healthcare professionals in Pakistan found that high levels of handwashing buffered the negative influence of burnout on mental health, 37 identifying another relation that merits attention.…”
Section: Discussionmentioning
confidence: 99%
“… 11–13 In addition, medical staffs are prone to anxiety when encountering emergencies. 10 , 14–16 Since December 2019, novel coronavirus pneumonia (COVID-19) has broken and swept worldwide. 17 …”
Section: Introductionmentioning
confidence: 99%
“…People who work in fields like "health", which directly benefit people and place a premium on interpersonal relationships, are more likely to experience burnout. 9,10 Anxiety is a risk factor for job burnout. [11][12][13] In addition, medical staffs are prone to anxiety when encountering emergencies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation